Dose-optimized computed tomography of the cervical spine in patients with shoulder pull-down: Is image quality comparable with a standard dose protocol in an emergency setting?. Issue 120 (November 2019) - Tozakidou, Magdalini; Yang, Schu-Ren; Kovacs, Balazs K.; Szucs-Farkas, Zsolt; Studler, Ueli; Schindera, Sebastian; Hirschmann, Anna
Highlights: Soft tissue and bone superimposition is a limiting factor in computed tomography of the cervical spine. Cervical spine CT with dose reduction showed no image quality impairment. Low shoulder position is crucial for optimization of CT-imaging of the cervical spine. Abstract: Purpose: Superimposing soft tissue and bony structures in computed tomography (CT) of the cervical spine (C-spine) is a limiting factor in optimizing radiation exposure maintaining an acceptable image quality. Therefore, we assessed image quality of dose-optimized (DO) C-spine CT in patients capable of shoulder pull-down in an emergency setting. Methods and materials: DO-CT (105mAs/120 kVp) of the C-spine in trauma settings was performed in patients with shoulder pull-down if C5 was not superimposed by soft tissue on the lateral topogram, otherwise standard-dose (SD)-CT (195 mAs/120 kVp) was performed. 34 DO (mean age, 68y ± 21; BMI, 24.2 kg/m 2  ± 3.2) and 34 SD (mean age 70y ± 19; BMI 25.7 kg/m 2  ± 4.4) iterative reconstructed CTs were evaluated at C2/3 and C6/7 by two musculoskeletal radiologists. Qualitative image noise and morphological characteristics of bony structures (cortex, trabeculae) were assessed on a Likert scale. Quantitative image noise was measured and effective dose (ED) was recorded. Parameters were compared using Mann-Whitney- U -test (p < 0.05). Results: At C2/3, DO-CT vs. SD-CT yielded comparable qualitative noise (mean, 1.3 vs. 1.0; p = 0.18) and morphological characteristics, but higher quantitative noise (27.2 ± 8.8HU vs. 19.6 ± 4.5HU; p < 0.001). At C6/7, DO-CT yielded lower subjective noise (1.9; SD-CT 2.2; p = 0.017) and better morphological characteristics with higher visibility scores for cortex (p = 0.001) and trabeculae (p = 0.03). Quantitative noise did not differ (p = 0.24). Radiation dose was 51% lower using DO-CT (EDDO-CT 0.80 ± 0.1 mSv; EDSD-CT 1.63 ± 0.2 mSv; p < 0.001). Conclusion: C-spine CT with dose reduction of 51% showed no image quality impairment. Additional pull-down of both shoulders allowed better image quality at lower C-spine segments as compared to a standard protocol.